Studi Kondisi Lingkungan, Analisis Vegetasi, dan Komponen Ekosistem di Hutan Universitas Diponegoro dan Kebun Pisang Mulawarman - Muhammad Iqbal Fauzan; Arafat, Septrial; Hamdi, Rifyal An Nesyafi (Produksi Tanaman, 2023)
This research was conducted on September 17 2022 in the Diponegoro University Forest and Mulawarman Banana Garden, Semarang. The tools used are raffia rope, scissors, tape measure, ruler, pegs, sticks, digital lux meter, anymetre, stationery and a camera. The materials used were Diponegoro University forest ecosystems and Mulawarman Banana Gardens as objects of observation. The observation method is by making a 20mx25m plot of land, in which a 5mx5m plot is made, and in it a 1mx1m plot is made 3 times. The 20mx25m plot analyzed the number, circumference, diameter, height of trees. 1x1 m plot was made 20cmx20cm plot 5 times, litter thickness was calculated. Plants in a 20m x 25m plot were analyzed for characteristics, biotic and abiotic factors present in Forest Ecosystems and Monoculture Ecosystems. The results of the research on abiotic factors show differences in temperature, humidity, intensity of solar radiation inside and outside the shaded area. The purpose of this research is to understand the difference in the amount of carbon sequestration at the research location.